2017
DOI: 10.1111/jmwh.12617
|View full text |Cite
|
Sign up to set email alerts
|

Risk For Postpartum Depression Among Immigrant Arabic Women in the United States: A Feasibility Study

Abstract: Findings of this study describe the prevalence of PPD in a sample of US immigrant women of Arabic descent and support the feasibility of a larger and more in-depth understanding of their immigration and acculturation experiences. Study participants reported high risk for PPD. Maternity blues and lack of social support were significant predictors to the risk for PPD. Future research tailored to this minority group is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Social support is a facilitator of well-being during both life transitions and stressful situations (Cohen & Wills, 1985). Research suggests that lower levels of social support are related to higher levels of maternal depression among immigrant and refugee women (Alhasanat et al, 2017;Chien et al, 2012;Dennis et al, 2017;Stewart et al, 2008Stewart et al, , 2012Tobin et al, 2017). Two studies have found that lack of social support predicted maternal depressive symptoms among immigrant Arab American mothers (Alhasanat, 2017;Alhasanat-Khalil et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Social support is a facilitator of well-being during both life transitions and stressful situations (Cohen & Wills, 1985). Research suggests that lower levels of social support are related to higher levels of maternal depression among immigrant and refugee women (Alhasanat et al, 2017;Chien et al, 2012;Dennis et al, 2017;Stewart et al, 2008Stewart et al, , 2012Tobin et al, 2017). Two studies have found that lack of social support predicted maternal depressive symptoms among immigrant Arab American mothers (Alhasanat, 2017;Alhasanat-Khalil et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the prevalence of PPD is estimated to be between 5% and 25% (Yonkers, Blackwell, Glover, & Forray, ). The prevalence of PPD among refugee and immigrant women is higher than for the general birthing population and estimated to be between 11% and 60% (Ahmed, Bowen, & Feng, ; Alhasanat, Fry‐McComish, & Yarandi, ; Tobin, Napoli, & Beck, ; Vigod et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Life changes, new responsibilities and unfamiliar childcare practices accom-Open Journal of Medical Psychology panied by the transition from pregnancy to maternity leave women isolated, alone and exhausted [27], moreover, becoming a mother is often a joyful but stressful event for many women, and involves a tremendous emotional, physical and social [28], in addition to participating in new development tasks [29]. With the grid, we are in prevention.…”
Section: Discussionmentioning
confidence: 99%